Artikel Ilmiah Agribisnis Analisis Perbandingan Produktivitas Tanaman Durian (Durio zibethinus) antara Indonesia dan Malaysia: Studi Deskriptif Kuantitatif Berdasarkan Data Tahun 2019–2023 - Ardilla, Riska; Lubis, Wildani; Nik Mohd Masdek, Nik Rozana (JURNAL AGRICA, 2025)
This study aims to analyze the comparison of durian (Durio zibethinus L.) productivity between Indonesia and Malaysia based on secondary data from 2019 to 2023. A quantitative descriptive method was applied by calculating the ratio between total production (tons) and cultivated area (hectares). The results indicate that although Indonesia has a much larger cultivation area, averaging 10.69 million hectares, its productivity remains low at around 0.11–0.16 tons/ha. In contrast, Malaysia, with an average of only 76 thousand hectares, achieved a significantly higher productivity level of 5.08–5.56 tons/ha. This difference is mainly due to the use of certified superior varieties such as Musang King, the implementation of intensive cultivation systems and modern agricultural technologies, and strong institutional support through national policies. Meanwhile, Indonesia’s durian productivity is still constrained by the use of uncertified seedlings, traditional farming techniques, and inefficient post-harvest management. The study concludes that improving durian productivity in Indonesia requires the strengthening of technological innovation, certified superior variety development, and the establishment of an integrated and sustainable agribusiness system to enhance competitiveness in the international market.